Analisis pengaruh pertumbuhan ekonomi, investasi, belanja daerah, inflasi dan upah terhadap kesempatan kerja di Provinsi Jambi - Deyana Desideria; Purwaka Hari Prihanto; Hardiani Hardiani (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2019)
The purpose of this research were to analyze the economic growth, investation, government expenditure, inflation, and wage the employment of Jambi Province. This research used ordinary least squares. The F test indicated that simultaneously the variables of the economic growth, investation, government expenditure, inflation, and wage significantly affected the employment of Jambi Province. While T test revealed that partially investation, government expenditure, and wage affected the employment of Jambi Province. Meanwhile, the variables of economic growth and inflation insignificant to the employment of Jambi Province. Keywords: Employmen Oppotunity, Investation, Government Expendicture, Wage.